STUDI KOMPARASI HASIL BELAJAR MATA PELAJARAN FIKIH ANTARA SANTRI PENGHAFAL AL-QUR’AN DAN SANTRI UMUM DI PONDOK PESANTREN AL-FALAH PUTERI - Anisa, Noor; Huda, Nuril (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to determine the comparison of learning outcomes of fiqh subjects between students who memorize the Koran and general students in class VIII at al-falah puteri Islamic boarding school. The population of this research is the VIII grade students at Al-Falah Islamic Boarding School, totaling 280 people. Which consists of 260 general students and 20 Quran memorization students. Because the number is not balanced, the Quran memorization students are taken as a whole, while the general students are taken by random sampling, namely by lottery, so the sample of this study was 40 people, consisting of 20 Quran memorization students and general students. The results of this study indicate that the learning outcomes of Jurisprudence subjects of students who memorize the Quran, from the categorization that has been done, it is known that the learning outcomes of fiqh subjects in the good category are 1 student with a percentage of 5%, in the sufficient category are 17 students with a percentage of 85%, and in the insufficient category are 2 students with a percentage of 10%. Based on the data analysis that has been carried out, the average value of the learning outcomes of fiqh subjects of Quran memorization students is 91.10. As for the analysis of the learning outcomes of general santri fiqh subjects, from the categorization that has been done, it is known that the learning outcomes of fiqh subjects in the good category are 3 students with a percentage of 15%, in the sufficient category are 12 students with a percentage of 60%, and in the insufficient category are 5 students with a percentage of 25%. Based on the data analysis that has been carried out, the average value of the learning outcomes of fiqh subjects for general students is 86.25. The results of data processing with SPSS show that the Sig. value of <0.01 is smaller than 0.05 so that the conclusion is that there is a significant difference in the two sample means. by comparing the magnitude of the two samples above, the Quran memorization students are significantly different (in this case better) when compared to general students.